Respons Verbal Anak Usia 5—6 Tahun pada Tindak Tutur Direktif Orang Tua - Sovia Wulandari (Balai Bahasa Provinsi Riau, 2018)
This study aims to explain the form of speech acts and speech strategies used by parents, as well as verbal responses of children aged 5—6 years on the speech acts of their parents. The method used is qualitative descriptive. The research subjects are children aged 5—6 years in 2012 and their parents. The results of this study indicate that the form of speech acts directive used by parents is enjoin, prohibit, suggest, and ask. The children's verbal response is the children responding positively to speech acts by telling a straightforward strategy with positive politeness and negative politeness; prohibit by a strategy of telling frankly with positive politeness, negative politeness, and vague; suggests with a straightforward strategy of no nonsense and negative politeness; and asks with a strategy of telling frankly with positive politeness gestures. In contrast, the children respond negatively to speech acts by means of a straightforward, frankly vague strategy; prohibit by the strategy of telling frankly without straight forward speaking; suggests a strategy of telling frankly with negative politeness gestures; and ask with a straightforward strategy without any preamble. Based on the results of the study, it can be concluded that parent should not use the strategy to speak frankly without for the act of telling, prohibiting, and asking. Meanwhile, for acts of speech of suggestion, parents should not use the strategy to speak frankly with the politeness of negative politeness because the children respond negatively in the form of rejection.